Geometry of the Magma Chamber and Curie Point Depth Beneath Hawaii Island: Inferences From Magnetic and Gravity Data - Mohamed, Ahmed; Al Deep, Mohamed; Abdelrahman, Kamal; Abdelrady, Ahmed (Frontiers in Earth Science, 2022)
This study used land gravity and airborne magnetic data to investigate the depth to the magmatic chamber and map the heat flow distribution beneath the active volcanoes of Hawaii Island using the Curie point depth (CPD) and gravity modeling. Obtaining some of the ground-based geophysical measurements was problematic due to accessibility limitations; therefore, this study used available data. The CPD and magnetic data were used to map the depth to the bottom of the magnetic layer by calculating the depth to the Curie isotherm (540°C) beneath Hawaii Island. The spectral peak method was used to calculate the depths to the shallow and deep magnetic sources for the entire island, and the CPD was calculated using the centroid method. A two-dimensional density model for two Earth layers was constructed using forward modeling of the gravity data. A large plume of dense intrusive material was observed beneath the three adjacent volcanoes of Mauna Loa, Mauna Kea, and Kilauea, and two small chambers were found to be located beneath the Kohala and Hualalai volcanoes. Based on the gravity modeling results, the depth to the magma layer varied from 0.5 to 10 km, and the heat flow was higher close to the volcanic eruption zones. The current study is informative and cost effective for the world’s most active volcanic areas.